An Inorganic Pac‐Man: Synthesis, structure and electrochemical studies of a heterometallic YCoII3W cluster sandwiched by two germanotungstates. Issue 17 (28th July 2022) - Ibrahim, Masooma; Mbomekallé, Israël M.; de Oliveira, Pedro; Bergfeldt, Thomas; Anson, Christopher E.
Abstract: A new heterometallic sandwich‐type Keggin polyoxometalate, [(GeW9 O34 )2 {YCo(W=O)(μ3 ‐O)(μ3 ‐OH)(μ2 ‐O)(μ2 ‐OH2 )(OH2 )(C2 H3 O2 )}] 13− has been synthesized by a simple reaction method. The isolated compound has been structurally characterized by single crystal X‐ray diffraction (SC‐XRD), Fourier transform infrared (FTIR) spectroscopy, elemental analysis, and thermogravimetric (TG) analysis. In addition, electrochemical properties have been investigated in detail. The X‐ray structure of this POM reveals that a unique heterometallic core {YCo3 (W=O)(μ3 ‐O)(μ3 ‐OH)(μ2 ‐O)(μ2 ‐OH2 )(OH2 )(OAc)} 7+ is sandwiched between two [GeW9 O34 ] 10− ligands, giving rise to the first example of a heterometallic core composed of 3d–4d–5d transition metal ions. Abstract :